ANALISIS MIKROTREMOR UNTUK MENGETAHUI KARAKTERISTIK TANAH DI SEKITAR JEMBATAN AMURANG, MINAHASA SELATAN: - - Handayani, Dewi; Agung Pratama, Deka; E Koagouw, Joanes; Nurfitriani (Pusdiklat BMKG, 2023)
Based on BNPB data, there has been landslide disaster due to abrasion that caused bridge and houses collapse in Amurang, South Minahasa on June 15, 2022. On geological map, the Amurang area classified as volcanic rock that is suspected to be Tondano’s Tuff when it exploded and formed Tondano’s Caldera. BMKG, in this case the Manado Geophysics Station, conducted a microtremor survei and analysed the data of the survei results using the Horizontal to Vertical Spectral Ratio (HVSR) method. This method can determine the value of the natural frequency and amplification of the soil which can be used to classify the soil at the survei location. The result show that the disaster area in Amurang is an alluvial rock formation formed from deltaic sedimentation, topsoil, mud, etc. with a depth of 30 meters or more. It does not match the classification given by the 1997 geological map. Keywords : natural frequency, HVSR, classification